Research-based Theatre about veterans transitioning home: A mixed-methods evaluation of audience impacts. (January 2022) - Nichols, Jennica; Cox, Susan M.; Cook, Christina; Lea, Graham W.; Belliveau, George
Abstract: Rationale: Contact!Unload, a research-based theatre production, portrays veterans experiencing mental health challenges and overcoming them through therapeutic enactment. It was performed eight times by veteran performers in 2017 for audiences in two Canadian cities comprised of civilians and military-connected personnel and their families ( n = 525). Methods: Drawing upon qualitative and quantitative data sources, this paper evaluates the immediate and longer-term impacts of Contact!Unload as a knowledge translation intervention for audience members. Results: Our findings suggest that the performance: 1) improved knowledge of mental health concerns and symptoms that some veterans experience when transitioning to civilian life, 2) increased knowledge of the need for mental health supports and care for veterans, 3) sustained impacts on awareness and knowledge six months after the play and 4) sparked dialogue and actions after the show for some audience members. Moreover, theatre was seen as a powerful medium to engage audience members both cognitively and affectively in the topic. Conclusions: Research-based theatre has significant potential as a knowledge translation intervention for mental health topics. The work also points to the untapped potential of using RbT to engage audience members in a mental health literacy intervention. Future work is needed to study how to effectively combine research-based theatre with intervention design frameworks and other mental health literacy interventions. Highlights: Research-based theatre (RbT) is an effective method for knowledge translation. The embodied experience of theatre bolsters empathy and receptivity to learning. Short and longer-term cognitive and affective impacts for audiences were achieved. RbT can also shift social responses to and professional practices in mental health. RbT holds untapped potential as a mental health literacy intervention.